2018
DOI: 10.1111/and.13213
|View full text |Cite
|
Sign up to set email alerts
|

Royal jelly protects male rats from heat stress‐induced reproductive failure

Abstract: Royal jelly (RJ) as an antioxidant has been shown to have attenuated oxidative stress damages in reproductive organs. The objective was carried out the effects of RJ on sperm characteristics, sperm malondialdehyde (MDA) concentration and in vitro fertilisation (IVF) outcome in heat stress (HS) exposed male rats. Forty-eight male rats were randomly divided into eight groups; group 1 received normal saline, group 2 received RJ (100 mg kg −1 day −1 ; PO), groups 3, 4 and 5 were heat-stressed (43, 39 and 37°C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Different properties of RJ have been shown previously and it has been revealed that RJ possesses a variety of biological activities including anti-oxidative, anti-tumor, antiinflammatory and repro-protective effects. 28,31,36,77,78 In the current study, concomitant administration of RJ to NIC receiving mice remarkably improved all NIC-induced negative changes in the oxidative stress and apoptotic statuses. The protection offered by RJ against NIC reproductive toxicity is likely thanks to its ability to reduce oxidative stress through neutralizing ROS as well as NICinduced RNA damage reduction.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Different properties of RJ have been shown previously and it has been revealed that RJ possesses a variety of biological activities including anti-oxidative, anti-tumor, antiinflammatory and repro-protective effects. 28,31,36,77,78 In the current study, concomitant administration of RJ to NIC receiving mice remarkably improved all NIC-induced negative changes in the oxidative stress and apoptotic statuses. The protection offered by RJ against NIC reproductive toxicity is likely thanks to its ability to reduce oxidative stress through neutralizing ROS as well as NICinduced RNA damage reduction.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, there have been increasing interests in the search of potential compounds being capable of minimizing the chemical‐induced reproductive toxicities. Different properties of RJ have been shown previously and it has been revealed that RJ possesses a variety of biological activities including anti‐oxidative, anti‐tumor, anti‐inflammatory and repro‐protective effects …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The co-administration of RJ and cod liver oil could improve the biochemical, hormonal, and structural aspects of testicular tissue in food yellow 4 (FY4)-induced rats [107]. The co-administration could effectively improve sperm characteristics and early embryo development as well as the sperm lipid peroxidation level by acting as a promising reproductive agent in heat-stress conditions [189].…”
Section: Effect On Fertilitymentioning
confidence: 99%